Phytochemical and antioxidant potential of selected plants from Mianwali, Pakistan - Saeed, Asma; Bhatti, Muhammad Zeeshan; Abidin, Sheikh Zain Ul; Khan, Raees; Saeed, Rida Fatima; Sabir, Maimoona; Kayani, Waqas Khan; Munem, Afifa; Chohan, Arshad Mahmood; Ahmed, Eman Ibrahim; et al. (Plant Science Today, 2022)
Plants have been used since ancient times as an important source of biologically active substances. Specific activities of these plant extracts are generally linked to the presence of secondary metabolites together with their phenolic contents. Present study aimed at investigating the total phenolic and flavonoid contents, and antioxidant activity of selected plants from five different families. The total phenolic content was measured using Folin-Ciocalteu assay and total flavonoid content by aluminum chloride colorimetric method. The antioxidant capacity was estimated by phosphomolybdinium assay. Our findings indicates that total phenolic content for methanolic extracts ranged from 27.07 to 59.11 mg GAE/g DW, and total flavonoid content ranged from 38.37 to 124.23 mg QE/g DW, with an antioxidant activity ranging from 55.82 to 129.06 mg AAE/g DE. Following trend was shown in the assessment of total phenolic and flavonoid contents: Rhazya stricta>Cicer arietinum>Solanum melongena>Solanum surattense>Solanum nigrum>Withania sominifera>Sisymbrium irio>Withania coagulans>Raphanus sativus>Fagonia indica>Brassica napus. While the antioxidant capacity followed the trend: Cicer arietinum>Solanum nigrum>Withania coagulans>Rhazya stricta>Raphanus sativus>Solanum melongena>Withania sominifera>Solanum surratense>Fagonia indica>Brassica napus>Sisymbrium irio. It is also seen that both wild and cultivated plants have higher medicinal value, which can be linked to the phenolic and flavonoid content, and antioxidant potential. Findings of the study revealed that wild plants possess higher phenolic content compared to cultivated plants, whereas cultivated plants had higher antioxidant activity.